ЛОГАРИФМИКАЛЫҚ ОЙЫС ФУНКЦИЯНЫ АНЫҚЛАЎДЫҢ ПРОГРАММАЛЫҚ ТӘМИЙНАТЫН ЖАРАТЫЎ - Аламинов, М.Х.; Жалелов, Р.М. (FAN va JAMIYAT, 2016)
The article deals with the study of working out the programme ensuring of the definition of logarithmic convexity of the given function.